Emerging therapeutic options for sporadic inclusion body myositis - Alfano, Lindsay N (Ther Clin Risk Manag, 2015)
Sporadic inclusion body myositis is the most common inflammatory muscle disorder preferentially affecting males over the age of 40 years. Progressive muscle weakness of the finger flexors and quadriceps muscles results in loss of independence with activities of daily living and eventual wheelchair dependence. Initial signs of disease are often overlooked and can lead to mis- or delayed diagnosis. The underlying cause of disease is unknown, and disease progression appears refractory to available treatment options. This review discusses the clinical presentation of inclusion body myositis and the current efforts in diagnosis, and focuses on the current state of research for both nonpharmacological and pharmacological treatment options for this patient group.